Custodiol versus Blood Cardioplegia: Comparison of Myocardial Immunohistochemical Analysis and Clinical Outcomes - Sen,Onur (2022)
ABSTRACT Introduction: Custodiol (histidine-tryptophan-ketoglutarate) and repetitive blood cardioplegia are the solutions for myocardial protection and cardiac arrest. In this study, we aimed to compare immunohistochemical analysis, clinical outcomes, and cardiac enzyme values of Custodiol and blood cardioplegia groups. Methods: This was a randomized prospective study consisting of 2 groups and 20 patients, 10 patients for each group, who underwent mitral and mitral/tricuspid valve surgery. Group 1 was formed for Custodiol cardioplegia and group 2 for blood cardioplegia. Perioperative and postoperative cardiac events were recorded, cardiac enzymes were analyzed with intervals, and myocardial samples were taken for immunohistochemical analysis. Recorded data were statistically evaluated. Results: There was no significant difference for the Custodiol and blood cardioplegia groups in perioperative and postoperative cardiac performance and adverse events. Cardiac enzyme analysis showed no significant difference between groups. However, two parameters (eNOS, Bcl-2) were in favor of the Custodiol group in immunohistochemical studies. Custodiol performed better in cellular oxidative stress resistance and cellular viability. Conclusion: Clinical outcomes and cardiac enzyme analysis results were similar regarding myocardial protection. However, Custodiol performed better in the immunohistochemical analysis.